A mini guide to Islamic derivative - Mohamed Sultan, Syed Alwi; Hasan, Aznan (Cert Publication, 2012)
This mini guide is intended to provide a quick snapshot and overview of the three common derivatives contracts - forward, options and swap- from an Islamic viewpoint.